The Influence of Family Moral and Ethical Understanding on Polite Behavior Among Seventh-Grade Students at MTs Darussalam - Nunung Nurasiah; Mohamad Abduh; Sri Rumiati (S&Co Publishing, 2026)
This study investigates the influence of students' understanding of moral norms and family ethics on polite behavior among seventh-grade students at MTs Darussalam Ciampea, Bogor. Using a quantitative correlational survey design conducted over four months, 30 students participated as the research sample. Data were collected through tests measuring moral norm understanding and structured questionnaires assessing family ethics and polite behavior. Descriptive analysis showed that students’ understanding of moral norms ranged from moderate to very high levels, while family ethics was consistently rated high to very high. In contrast, students’ polite behavior varied from low to high levels, indicating differences in behavioral implementation despite generally positive moral and ethical conditions. Inferential analysis confirmed normal distribution and linear relationships among variables. Hypothesis testing showed that both moral norm understanding and family ethics significantly and positively influenced polite behavior, with family ethics emerging as the stronger predictor. Moreover, simultaneous analysis revealed that the two independent variables jointly exerted a significant influence on students’ polite behavior. These findings suggest that students' politeness is shaped by the integration of moral understanding and ethical family practices. Strengthening school-family collaboration is therefore essential to support character development and sustain polite behavior among students.